Community Development in Kemijen Village, East Semarang: A Corporate Social Responsibility in Practice - Hartuti Purnaweni; Irzaldi Yazid; Mutia Nur Arifah; Anis Qomariah (Jurnal Ilmu Lingkungan, 2021)
Companies, either state-owned and private which operates in the field and/or related to natural resources must implement Corporate Social Responsibility (CSR), such as by PT Indonesia Power (PT. IP) UBP-Tambaklorok which is located nearby Tanjung Mas Harbor, Tambaklorok Village, North Semarang District. Semarang City. The CSR implementation should benefit for both sides, the company for its image and the local community for the implemented programs. Therefore it is important to analyse perception of the local community as well as their opinions about the company's CSR activities in their village, in this case is the people of Kemijen village which is located adjacent to the PT. IP’s area. This research is descriptive qualitative, done in 2019, describing the phenomenon of CSR implementation by PT. IP, and the perception of the local community of Kemijen village towards the CSR activities implemented by PT. IP. The informants were taken using purposive sampling technique, covering both formal and informal leaders, the local people, as well as community development officer of PT. IP. Primary data was gathered using in-depth interview technique and observation. Secondary data consist of documents. Primary and secondary data was then coded and analysed interactively. PT. IP has formulated and implemented the Company’s strategies into CSR Roadmap 2015-2019, which is the grand strategy and a milestone of CSR implementation to integrate CSR strategy into the Company’s strategy, in the sectors of education, health, economy, and infrastructure. According to the perception of the Kemijen villagers, there have been both benefit and insufficiency of the PT. IP’s CSR implementation. They expect more programs to be implemented, in order to allowing them more opportunities for poverty alleviation.